Wastewater treatment options for paper mills using recycled paper/imported pulps as raw materials: Bangladesh perspective (Chemical Engineering Research Bulletin, 2010)
Paper sector in Bangladesh is currently expanding day-by-day to meet the increasing demand of industrial, writing/printing and specialty papers. Paper mills have adverse eects on the environment by producing huge quantity of wastewater. Yearly, approximately 14 million m3 wastewater is being discharged to the surface water bodies and irrigated lands without no/limited treatment. Water pollution from pulp and paper mills can be minimized through proper effuent characterization and design of appropriate treatment facilities. In this article dierent techniques of wastewater treatment for paper mills are discussed. Case study based on treatability analysis and jar test for a paper mill producing 200 m3/h of effuent is provided. On the basis of the case study a simplified treatment process is proposed. Proper treatment of such mills would not only save our environment but can also be beneficial for the industries by water usage minimization.Keywords: Pulp and paper mills; recycled paper; imported pulp; environmental impact; wastewater characterization; wastewater treatmentDOI = 10.3329/cerb.v14i1.5236 Chemical Engineering Research Bulletin 14 (2010) 65-68